Chrome Tanning Leather of Giant Sea Perch Combined with Seed Extract Areca Nut on the Physical Characteristics - Bustami - Ibrahim; Ella - Salamah; Nurul - Hak; Ade Komalasari Suhendar (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Tanning is the process of converting raw hide protein to leather, which are stable, not easily decompose, and is suitable for a variety of uses. The use of vegetable based tanning materials in the leather tanning process has not been carried out. Vegetable based materials that were used are betel nuts. This plant contains tannin which is the main agent in the process of leather tanning. The aim of this study was to determine the physical characteristics of snapper leather treated with betel nut extract. Soxhlet extracting method with methanol as a solvent were used to obtain tannin from betel nuts. Tanned Snapper Leather were analyzed for physical quality, elongation strength, tensile strength, tear strength, and sewing strength. The result showed that methanol extracted betel nut with 10% concentration gives the optimum physical characteristics.Keywords: areca nut, chrome, snapper, snapper